Limitations of the Freedom of Speech: Issue of the Infallibility of Prophets and United Nations - Farooq Abdullah; Muhammad Abdullah (Journal of Islamic and Religious Studies, 2018)
West generally blames the Muslim world on the grounds that it does not accede to freedom of expression. But in fact, Islam gave the right of freedom of expression for the first time in history. In Rome before Islam was introduced, the rulers used to enslave the masses. Greek ministers, Roman Catholic pastorates, Spanish Inquisitions and the ministerial experts used to rebuff the individuals who used to articulate unapproved religious perspectives. The British Parliament passed a Bill of Rights in 1689. This bill proclaimed the right to speak freely. It returned amid the French Revolution of 1789 which declared speaking freely as a natural right of each person. As indicated by Holy Quran there might be no impulse in acknowledgment of the religion which is also proved from Sunnah and through the actions of the companions of Prophet Muhammad (PBUH). Blasphemy law is a law related to blasphemy, or irreverence toward holy prophets, or beliefs or religious traditions. In the provisions of Article 18 and 19 of the U.N. Charter, no limitations were made for expression which has left the room open for the defamation on name of freedom of speech. According to Islam, maintaining the honor and respect of all people is essential for regional, national and universal peace. Any articulation which abuses peace, honor and pride of any individual, race, religious gathering or any minority assembly as a rule and so forth cannot be incorporated into the meaning of flexibility of articulation or freedom of speech.